Recruitment and Retention of International Students in Canada During the Pandemic: An Analysis of Immigration Policy Measures - Garcia-Sitton, Isaac (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2025)
This paper examines Canada’s immigration policy measures during the COVID-19 pandemic and their impact on international student recruitment and retention. Applying multiple streams analysis (MSA), it explores how the problem stream (pandemic disruptions), policy stream (immigration changes), and politics stream (government priorities) intersected to shape policy responses. Using qualitative document analysis, the study reviews federal policy documents from March 2020 to December 2022, covering key measures such as travel regulations, online learning provisions, work-related policies, and pathways to permanent residency. Findings indicate a significant shift in policymaking from reactive to proactive strategies, emphasizing economic recovery as immediate health threats diminished. The pandemic necessitated rapid policy innovation, particularly in online learning and work-related provisions, which may influence future approaches to international education and immigration in Canada. The paper concludes with a discussion on the implications of these policies and recommendations for future research to understand their long-term effects on Canada’s international education sector.